"The Drum is Your Document": Decolonizing Research Through Anishinabe Song and Story. Issue 4 (February 2016) - Pedri-Spade, Celeste
Drawing upon Indigenous ways of knowing and the revitalization of Indigenous education, the author, as Anishinabekwe, 1 "storysharer, " and drummer, explores the relationship between song and story in Anishinabe hand drumming and how this relationship both guides and reveals Anishinabe knowledge. To decolonize the research journey, the author turns to her relationship with her drum and its teachings of holism, relationality, and interconnectedness. The author explores how the teachings and interpersonal relationships centred around the drum help direct the production of a short documentary film. 2 What ensues is a project that honours the ways Anishinabeg 3 create and share knowledge and draws on performance (auto)ethnographic techniques to show rather than tell, thereby engaging both the hearts and minds of the audience. The author highlights conceptions of care, faith, and thanks in articulating a creative Indigenous methodology that is about "doing good work."